Quirl : Künstlersymposion : auf dem "jagenberg-gelände" in düsseldorf. (Düsseldorf : [s.n.], 1986)
Beckert, Jutta ; Bell, Victoria ; Doerbecker, Sander ; Eastes, Heather ; Ebersbach, Hartwig ; Geismar, Jarg M. ; Glasmeier, Rolf ; Greub, Charlott ; Hausmann, Till ; Hertzfeldt, Roger ; Jewell, Dick ; Passow, Beate ; Ohlow, Eva ; Reader, Stephen ; Salentin, Gerlinde ; Santarossa, Hella ; Schirmer, Günter M. ; Staeck, Klaus ; etc.
Quirl : Künstlersymposion : auf dem "jagenberg-gelände" in Düsseldorf, 22.9.1986 bis 19.10.1986
boek